Comunicação institucional: a aplicação das ferramentas no segmento petshop na região central de São Sebastião. - MACEDO, Cleber dos Santos; SANTOS, Juliana dos (189, 2016)
Esta pesquisa teve como intuito apresentar a vertente Comunicação Institucional, que compõe a Comunicação Empresarial Integrada, e sua aplicação nas microempresas. Existem muitos fatores que interferem na tomada de decisão do administrador e consequentemente na formação e consolidação de uma organização. O objetivo deste trabalho é demonstrar os fatores internos e externos que dificultam a aplicação da vertente em duas microempresas do segmento de petshop, situadas na região central de São Sebastião. Por se tratar de um assunto novo e que vem crescendo no nosso país, o tema torna-se extremamente relevante principalmente no âmbito acadêmico, pois poderá auxiliar na formação de novos gestores. O trabalho desenvolvido pelo método de pesquisa bibliográfica e de campo, com amostragem não probabilística intencional, de natureza qualitativa e descritiva, busca apresentar os conceitos teóricos do tema pesquisado, além de relatar a realidade do cenário vivido pelos dois microempresários de São Sebastião entrevistados, descrevendo a percepção destes gestores em relação à vertente em estudo. Feito uma análise nas respostas das entrevistas percebeu-se as dificuldades enfrentadas pelos gestores. E após o levantamento de todas as informações necessárias foi possível constatar que não existe a aplicação da Comunicação Institucional de forma efetiva por parte dos dois microempresários. Palavras-chave: Comunicação Institucional. Vertente. Aplicação. Fatores. ABSTRACT This research was intended to present the Institutional Communication component, which makes up the Integrated Business Communication, and its application in micro-enterprises. There are many factors that interfere with the administrator's decision-making and consequently the formation and consolidation of an organization. The objective of this study is to demonstrate the internal and external factors that hinder the implementation of strand two petshop segment of microenterprises, located in central of São Sebastião. Because it is a new subject and that is growing in our country, the issue becomes extremely relevant mainly in the academic sphere, as this may assist in training new managers. The work carried out by the method of literature and field research with non-probability sampling intentional, qualitative and descriptive nature, seeks to present the theoretical concepts of the research topic, in addition to reporting the reality of the scenario experienced by both microentrepreneurs of São Sebastião respondents describing the perception of managers regarding the present study. Made an analysis of the responses of the interviews realized the difficulties faced by managers. And after the lifting of all necessary information it was found that there is no application of Corporate Communications effectively by the two microentrepreneurs. Keywords: Corporate (Texto elaborado pelos autores e extraído do trabalho original.)This research was intended to present the Institutional Communication component, which makes up the Integrated Business Communication, and its application in micro-enterprises. There are many factors that interfere with the administrator's decision-making and consequently the formation and consolidation of an organization. The objective of this study is to demonstrate the internal and external factors that hinder the implementation of strand two petshop segment of microenterprises, located in central of São Sebastião. Because it is a new subject and that is growing in our country, the issue becomes extremely relevant mainly in the academic sphere, as this may assist in training new managers. The work carried out by the method of literature and field research with non-probability sampling intentional, qualitative and descriptive nature, seeks to present the theoretical concepts of the research topic, in addition to reporting the reality of the scenario experienced by both microentrepreneurs of São Sebastião respondents describing the perception of managers regarding the present study. Made an analysis of the responses of the interviews realized the difficulties faced by managers. And after the lifting of all necessary information it was found that there is no application of Corporate Communications effectively by the two microentrepreneurs. Keywords: Corporate Communications. Shed. Application. Factors.(Texto elaborado pelos autores e extraído do trabalho original.)
Keywords: Comunicação na administração; Gestão e Negócios